2017
DOI: 10.3390/su9060899
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Corporate Performance Prediction Model Considering Technical Capability

Abstract: Many studies have predicted the future performance of companies for the purpose of making investment decisions. Most of these are based on the qualitative judgments of experts in related industries, who consider various financial and firm performance information. With recent developments in data processing technology, studies have started to use machine learning techniques to predict corporate performance. For example, deep neural network-based prediction models are again attracting attention, and are now wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Recently, with the outstanding performance in various classification problems [27,28], there have been attempts to apply deep learning techniques to stock market prediction. Deep learning techniques have achieved remarkable success in numerous prediction tasks, since they can extract useful features automatically during the learning process [29,30].…”
Section: Stock Market Predictionmentioning
confidence: 99%
“…Recently, with the outstanding performance in various classification problems [27,28], there have been attempts to apply deep learning techniques to stock market prediction. Deep learning techniques have achieved remarkable success in numerous prediction tasks, since they can extract useful features automatically during the learning process [29,30].…”
Section: Stock Market Predictionmentioning
confidence: 99%
“…They found that business performance predictions are related to the industries. Lee et al (2017) proposed a deep neural network-based performance prediction model using financial and patent indicators.…”
Section: Business Performance Measurement and Prediction -Related Workmentioning
confidence: 99%
“…Furthermore, it proves that DBN outperforms the SVM. Lee et al (2017) tackled the bankruptcy prediction problem based on DBN which use RBM. The built model includes two phases: (1) unsupervised learning phase and (2) a finetuning phase.…”
Section: Deep Learning Algorithmsmentioning
confidence: 99%